2021
DOI: 10.1001/jamainternmed.2021.0242
|View full text |Cite
|
Sign up to set email alerts
|

Advertising or Evidence?—Why We Need System Changes in Academia to Improve Media Reporting

Abstract: Limitations include use of a measure of EHR work that considers only when clinicians are actively working (thus likely underestimating total time spent on the EHR), a focus on ambulatory practices, an inability to describe the breakdown of after-hours activity, and lack of accounting for time spent by scribes on documentation.The interspecialty differences we have identified are important given the known associations between administrative burden and clinician burnout. Further investigation should seek to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Researchers cannot underestimate the importance of cowriting these press releases with their communications colleagues. As pointed out in the Invited Commentary by McCartney, recent research has found a strong association between exaggerated news and overstated press releases . Furthermore, when medical professionals are interviewed by journalists or asked for their opinion on research or health news, they should be keenly aware of the substantial influence that any overstated or premature claims can have on patient expectations.…”
mentioning
confidence: 99%
“…Researchers cannot underestimate the importance of cowriting these press releases with their communications colleagues. As pointed out in the Invited Commentary by McCartney, recent research has found a strong association between exaggerated news and overstated press releases . Furthermore, when medical professionals are interviewed by journalists or asked for their opinion on research or health news, they should be keenly aware of the substantial influence that any overstated or premature claims can have on patient expectations.…”
mentioning
confidence: 99%